Testing trace-element distribution and the zr-based thermometry of accessory rutile from chromitite - Zaccarini, Federica; Garuti, Giorgio; Luvizotto, George L. [UNESP]; de Melo Portella, Yuri; Singh, Athokamp K. (MDPI, 2021)
Trace element distribution and Zr-in-rutile temperature have been investigated in accessory rutile from stratiform (UG2, Merensky Reef, Jacurici), podiform (Loma Peguera), and metamorphic chromitites in cratonic shields (Cedrolina, Nuasahi). Rutile from chromitite has typical finger-print of Cr-V-Nb-W-Zr, whose relative abundance distinguishes magmatic from metamorphic chromitite. In magmatic deposits, rutile precipitates as an intercumulus phase, or forms by exsolution from chromite, between 870 °C and 540 °C. The Cr-V in rutile reflects the composition of chromite, both Nb and Zr are moderately enriched, and W is depleted, except for in Jacurici, where moderate W excess was a result of crustal contamination of the mafic magma. In metamorphic deposits, rutile forms by removal of Ti-Cr-V from chromite during metamorphism between 650 °C and 400 °C, consistent with greenschist-amphibolite facies, and displays variable Cr-Nb, low V-Zr, and anomalous enrichment in W caused by reaction with felsic fluids emanating from granitoid intrusions. All deposits, except Cedrolina, contain Rutile+PGM composite grains (<10 µm) locked in chromite, possibly representing relics of orthomagmatic assemblages. The high Cr-V content and the distinctive W-Nb-Zr signature that typifies accessory rutile in chromitite provide a new pathfinder to trace the provenance of detrital rutile in placer deposits.
Keywords: Chromite deposits; Magmatic crystallization; Metamorphism; Rutile; Trace elements; Zr-in-rutile thermometry